Pengaruh Kepuasan Kerja Terhadap Komitmen Organisasi - Maria Puspita Sari; Mathilda Sri Lestari; Suprapto Suprapto (Program Studi Teknik Industri Universitas Setia Budi, 2021)
Company employees as human resources are important capital that must receive high attention by companies, including construction companies. Along with the rapid growth of the construction sector, construction activities are carried out evenly in various regions in Indonesia, one of which is in the Sukoharjo district. Employees will tend to leave the organization if they are not satisfied with the work climate and job characteristics. Employees will have a high organizational commitment when they are satisfied with their work, supervision, salary, promotion and co-workers. This study aims to identify the effect of employee job satisfaction on organizational commitment by taking a case study on a construction company in the Baki sub-district, Sukoharjo. Data was collected by distributing questionnaires to 30 construction company employees. The data processing method used was linear regression. The results showed that there was a positive and significant relationship between job satisfaction and organizational commitment. Keywords: job satisfaction, organizational commitment, construction employees, linear regression